LABORATORY INVESTIGATION OF OIL STRIPPING FROM CORE PORE SPACES BY SURFACTANT SPONTANEOUS IMBIBITION PROCESSES AT HIGH TEMPERATURE - Maurich, David (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2023)
Large amounts of oil are still trapped in the microscopic pore spaces of the rock during the primary and secondary recovery processes as a result of competition between the viscous forces and the capillary forces that arise from the interfacial tension (IFT) between the oil and water phases which causes the injected water to pass through the residual oils. To recover the remaining oils, the capillary pressure between the fluids must be significantly lowered by reducing the IFTs with surfactant. The selection of the best surfactant that is suitable for reservoir fluids and rocks in harsh reservoir conditions through laboratory studies is critical before conducting a field surfactant injection. Compatibility of surfactant with reservoir conditions such as reservoir temperature, high formation water salinity and rock absorption of surfactant molecules is a major challenge in the field surfactant injection. The best surfactant should be compatible with reservoir fluids and rocks and capable of increasing the efficiency of microscopic displacement and oil recovery factor. This investigation was aimed to provide valuable information about the recovery processes of oil stripping in microscopic pore spaces of core samples by spontaneous imbibition of surfactant molecules under high reservoir temperature conditions. The spontaneous imbibition processes were conducted in Amott imbibition cells. The process of the fluids interactions and oil recovery was observed and also recorded for further analysis and calculations. The results showed that non-ionic surfactants were more stable and performed better capability in stripping and recovering oil from core samples at high reservoir temperature.